A PRÁXIS DISCURSIVA DE PRODUÇÃO DE TEXTO: CONEXÕES ENTRE EDUCAÇÃO E ENUNCIADOS CONCRETOS DOS SUJEITOS DO CAMPO - Freitas, Lenice Garcia de (2020)
This study analyzes the social reality of students of a rural school as starting and arrival point to pedagogical practice of text production, establishing connections between education and concrete enunciations of the learners. From the perspective of th